2020
DOI: 10.1016/j.jad.2019.11.088
|View full text |Cite
|
Sign up to set email alerts
|

Prospective relationships of mentally passive sedentary behaviors with depression: Mediation by sleep problems

Abstract: Background: As distinct from mentally-active sedentary behaviors (e.g. reading), passive sedentary behaviors (e.g. TV-viewing) have been linked to a higher risk of depression, but the underlying mechanisms are unclear. We examined the potential mediating role of sleep problems in prospective relationships of passive sedentary behaviors with major depressive disorder (MDD). Method: In 1997, 43 863 adults were surveyed and responses linked to clinician diagnoses of MDD until 2010. The questionnaire included item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
1
22
3
2
Order By: Relevance
“…Considering the times before the COVID-19 pandemic, movement behaviors were associated with mental health [ 8 ] as well as sleep quality [ 10 , 12 ] and sleep quality was prospectively associated with mental health [ 26 ]. In this sense, sleep quality could act as a mediator of the association between movement behaviors and mental health [ [16] , [17] , [18] ]. Therefore, our findings agree with previous studies from before quarantine [ [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the times before the COVID-19 pandemic, movement behaviors were associated with mental health [ 8 ] as well as sleep quality [ 10 , 12 ] and sleep quality was prospectively associated with mental health [ 26 ]. In this sense, sleep quality could act as a mediator of the association between movement behaviors and mental health [ [16] , [17] , [18] ]. Therefore, our findings agree with previous studies from before quarantine [ [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, sleep quality could act as a mediator of the association between movement behaviors and mental health [ [16] , [17] , [18] ]. Therefore, our findings agree with previous studies from before quarantine [ [16] , [17] , [18] ]. However, these results suggest that the association between the incidence of unhealthy movement behaviors and mental health can be mediated by worsening sleep quality even in relatively short periods of movement deprivation and quarantine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight-loss maintainers and controls also did not appreciably differ in time spent sitting while reading or studying, traveling, or talking/texting/socializing. These could be considered more mentally active forms of sedentary behavior (29,30). Interestingly, prior research has suggested that substituting passive with mentally active sedentary behaviors or physical activity may have beneficial health effects (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…These could be considered more mentally active forms of sedentary behavior (29,30). Interestingly, prior research has suggested that substituting passive with mentally active sedentary behaviors or physical activity may have beneficial health effects (29)(30)(31). Current behavioral weight-loss interventions tend to target a reduction in time spent watching TV.…”
Section: Discussionmentioning
confidence: 99%